CHOICE EFFECT OF INPUT ACTION MODELS ON MEASURING ACCURACY FOR EXTENDED KALMAN FILTERS - P. A. Khmarski; A. S. Solonar (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Choice effect of input action models on measuring accuracy for Extended Kalman filters is considered. Recommendations about practical application of Extended Kalman filter modifications are listed.